Digital Twins: A Solution Under the Standard k-ε Model in Industrial CFD, to Predict Ideal Conditions in a Sugar Dryer - Verónica Guerrero-Hernández; Guillermo Reyes-Morales; Violeta Alejandra Bastián Lima; Jorge Ortega-Moody; Quelbis Román Quintero Bertel; Gerardo Aguila Rodríguez; Blanca Estela González Sánchez; Claudia Ceballos-Díaz; Luis Carlos Sandoval Herazo (Fluids)
Currently, emerging technologies such as digital twins, through the application of frontier techniques, have achieved physics-based simulations that reduce time and costs. Hence, its application is of the utmost importance in the industry, mainly in the sugar drying process of sugar mills for an updated version of the process. Sugar mills lack process control, leading to unexpected issues. Sugar mills with poor process control cause operational problems. This article presents significant innovation in the field of industrial process optimisation through the integration of digital twins with the k-ε standard model in computational fluid dynamics (CFD). The primary objective of this publication is to predict the ideal conditions of a centrifugal sugar dryer using CFD through the k-ε standard model to analyse the aerodynamic behaviour of the ambient air by applying heat through heat exchangers to obtain a suitable mass flow. The mathematical model was carried out under an energy balance to the thermodynamic system to study the behaviour through a simulation in MATLAB R2017 and an air-fluid simulation of drying with software CFD 2015. The results proved that the model of the thermal system and frontier conditions, when applying CFD, carried our simulation and remained stable. The ideal operating conditions of the centrifugal sugar dryer can be predicted effectively, with an energy saving of 4.25%.